CHA2DS2-VASc score, left atrial size and atrial fibrillation as stroke risk factors in the Tromsø Study. Issue 2 (6th September 2016) - Tiwari, Sweta; Løchen, Maja-Lisa; Jacobsen, Bjarne K; Hopstock, Laila A; Nyrnes, Audhild; Njølstad, Inger; Mathiesen, Ellisiv B; Schirmer, Henrik
Abstract : Objective: CHA2 DS2 -VASc score, left atrial (LA) size and atrial fibrillation (AF) have individually been associated with stroke risk. Our aim was to investigate the predictive ability of combinations of these factors for the odds of incident stroke in a population-based cohort study. Methods: We followed 2844 participants from the Tromsø Study from 1994 to 2012. Information on LA size and CHA2 DS2 -VASc score (age, sex, congestive heart failure, hypertension, vascular disease, stroke and diabetes) were obtained at baseline. AF status was recorded from medical records. The outcome measure was all strokes. The association between covariates and stroke was investigated by means of multivariate logistic regression analysis. Results: A total of 325 participants (45% women, mean age at baseline 59.3 years) had a stroke. Incidence rates for stroke were 6.4 in women and 8.4 in men per 1000 person-years. Participants with CHA2 DS2 -VASc ≥1 and LA size <2.8 had ∼4 times (95% CI 2.6 to 5.3) increased odds of stroke, whereas participants with CHA2 DS2 -VASc ≥1 and LA size ≥2.8 had ∼9 times (95% CI 5.3 to 16.4) increased odds of stroke, compared with participants with CHA2 DS2 -VASc score 0, irrespective of AF status. Adjustment for significant covariates had minimal impact on the OR estimates. Conclusions: Combining CHA2 DS2 -VASc score ≥1 and enlarged LA size identified participants with high odds of stroke regardless of AF status.